The FML (Fucose Mannose Ligand) of Leishmania donovani: a new tool in diagnosis, prognosis, transfusional control and vaccination against human kala-azar - Claris B. Palatnik de Sousa; Elza M. Gomes; Edilma Paraguai de Souza; Wania R. dos Santos; Sirley R. de Macedo; Linnete V. de Medeiros; Kleber Luz (Sociedade Brasileira de Medicina Tropical (SBMT), 1996)
The Fucose-Mannose Ligand (FML) of Leishmania donovani is a complex glycoproteic fraction. Its potential use as a tool for diagnosis of human visceral leishmaniasis was tested with human sera from Natal, Rio Grande do Norte, Brazil. The FML-ELISA test, showed 100% sensitivity and 96% specificity, identifying patients with overt kala-azar (p < 0.001, when compared to normal sera), and subjects with subclinical infection. More than 20% apparently healthy subjects with positive reaction to FML developed overt kala-azar during the following 10 months. In the screening of human blood donnors, a prevalence of 5% of sororeactive subjects was detected, attaining 17% in a single day. The GP36 glycoprotein of FHL is specifically reconized by human kala-azar sera. The immunoprotective effect of FML on experimental L. donovanii infection was tested in swiss albino mice. The protection scheemes included three weekly doses of FML, supplemented or not with saponin by the subcutaneous or intraperitoneal routes and challenge with 2x 10(7) amastigotes of Leishmania donovani. An enhancement of 80.0 % in antibody response (p<0.001) and reduction of 85.5 % parasite liver burden (p<0.001) was detected in animals immunized with FML saponin, unrespectivety of the immunization route. O FML (Ligame de Fucose-Manose) de Leishmania donovani é uma fração glicoproteica complexa. O seu potencial no diagnóstico da leishmaniose visceral humana foi testado com soros provenientes de Natal, Rio Grande do Norte, Brasil. O teste de FML-ELISA mostrou 100% de sensibilidade e 96% de especificidade, identificando pacientes com calazar declarado (p<0.001, comparados com soros normais) e indivíduos com infecção subclínica. Mais de 20% dos sororreativos assimptomáticos desenvolveram a doença no prazo de 10 meses. Na análise de doadores de sangue, 5% de sororeativos, atingindo até 17% num único dia foram detectados. A glicoproteínaGP36 do FHL é reconhecida especificamente por soros de pacientes com calazar. O potencial imunoprotetor do FML no ...